Implementación de la contabilidad comercial por el sistema de cuenta múltiple en la empresa del señor Edgar Antonio Arias Córdova, cantón Catamayo período agosto – septiembre 2014 - Córdova Jumbo, Blanca Graciela (2015)
The proposal of this research paper entitled: "IMPLEMENTATION OF BUSINESS ACCOUNTING SYSTEM OF MULTIPLE ACCOUNT IN THE COMPANY OF THE LORD EDGAR ANTONIO ARIAS CÓRDOVA, CANTON CATAMAYO PERIOD AUGUST - SEPTEMBER 2014", is performed as a prerequisite to obtaining the title of Engineer in Accounting and Auditing, CPA. and implement the knowledge acquired in the National University of Loja, mode Schooling, which it is hoped that this work will gconstitute a contribution to the company under study, to deliver this useful accounting tool to all stakeholders especially to administration, here a real, reliable and reasonable financial company information will be provided and thus maximize profit and aggrandizement of the company contributing to the social and economic development of this important sector of the country to generate resources and employment. The implementation of the accounting process meets all the objectives on which the Plan and User Accounts ability to properly encode the registration of economic operations of the company is made, the initial inventory of the assets, rights and obligations rises the company based on the source documents with the corresponding state of the initial situation, journaled all economic movements during the period August-September 2014 to the preparation of financial statements. After done the accounting process could have a clearer view of the financial and economic situation of the company, with the main findings and conclusions, where the main thing is that you should continue with the implementation of accounting system that allows you to have the timely and reliable financial information